Developing An Intelligent Maintenance DSS for Diagnosing Pump Faults Using Case-Based Reasoning Approach - Alhaam Mansour Aleisawi; Saleh M. Amaitik (African Journal of Advanced Pure and Applied Sciences, 2026)
This research paper presents a study on the development of an intelligent decision support system (DSS) for diagnosing pump faults using Case-Based Reasoning (CBR). The system was designed and tested using data from the Arabian Gulf Oil Company (AGOCO), focusing on centrifugal pumps. The (CBR), is a relatively recent problem-solving technique that is attracting increasing attention and this technique provide a good solution in pump maintenance problems. Following the basic idea in CBR, experiences in solving previous similar pump maintenance problems are used to find the solutions for new problems. Good results are obtained from a wide range of experiments, and the results of the work are evaluated and some directions from this work are obtained.